Simulation of Torsion Vibration of Power Transmission Shaft in Marine Propulsion System using MATLAB - صالح, الهادي; عواطف نصره; منى اسبر; محمد خنيسي (Latakia University Journal -Engineering Sciences Series, 2024)
This research programmed and simulated the torsional vibrations affecting the capacity transfer shaft of the ship's propulsion station and assessed its impact on it both in the early design stages and during investment. Natural and forced frequencies, mode shape, and Campbell schemes were initially calculated, and the critical rotation speed at which the resonance occurs was determined to identify critical positions exposed to maximum stress. These calculations were made by modeling the rotary mass power station using Matlab software. Predicting vibration forms and critical rotation speed will allow the determination of the resonance field and thus propose design and investment solutions to reduce the causes of torsional vibration and mitigate its catastrophic damage to the propulsion system. Several analytical methods have been used to make calculations and compare these methods with each other. The propulsion system is assumed to be a linear system, and the inflammatory forces affecting it are harmonic forces. Ultimately, the proposed solution algorithm will be applied to a propulsion system for a real commercial ship with known characteristics and parameters.